Mothercare : down or flourishing? - Mehta, Anupam; Saha, Jyotirmoy; Mazumder, Sumit; Xiao, Ling, active 2022 (London : SAGE Publications : SAGE Business Cases Originals, 2022)
Mothercare is a British retailer specialising in expectant mother and kids wear, with a market capitalisation of GBP 74.99 million (July 2021). Mothercare has been experiencing financial troubles for a couple of years, with a net loss of GBP 76 million in 2018, which increased to GBP 93 million in 2019. In November 2019, the company closed all stores in the UK. The UK retail segment was put in administration as it was in debt and could not pay the money it owed. Students will be asked to answer why the company had to do so, and if the company will be able to survive and, if so, how? The case provides detailed information about the UK and the international segments (including both online and in-store) sales and profitability from 2015 to 2020, which allows an examination the financial performance, focusing on the continuing operating segments and the direction of growth. The case enables the student to dig deeper into the company's operating segment analysis rather than analyse the company's overall financial performance as a whole.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mothercare (Firm) -- Case studies; Corporate turnarounds -- Case studies